(untitled) (Herald of Journalism, 2024)
The purpose of the research is to study the historical and theoretical foundations of Kazakh journalism and to scientifically analyze the formation of traditional publications in accordance with the requirements of new media. And the idea of the research work is to assess innovative growth in the information space and media migration as an example of a national phenomenon. The development of technology has brought various changes to the world of information and communication, as in any field.Together with the"information age", such concepts as"new media","social networks","digital art" have entered our life order, our customs and consciousness.This is the beginning of a new era.In journalism, these turns are seen as a kind of change in the dissemination of news and information, that is, a transition from traditional media to new media.This study began with taking into account the dynamics of traditional media and traditional methods of news dissemination, with a creative and technical selection of the logic and decisiveness of the formation in national journalism.Later, the process of transition from traditional media to new media was determined and evaluated according to the standards of historical dynamics.There was an attempt to determine how and to what extent the transformation of the new media environment influenced the sources of national journalism.In this study, the analysis of changes in the world of national journalism in the process of transition of traditional media to new media was carried out, the literature was reviewed, the creative search and creativity of print journalists was analyzed, and the features of new media in the dissemination of national information were identified. The natural formation of traditional mass media ("Egemen Kazakhstan", "Kazakh literature", "Aikyn" newspapers) was assessed as the scientific and practical value of the mentioned research work. At the same time, it was intended to give an impetus to the research on the integration of traditional media. Comparative and historical methods were used as research methodology.